PENERAPAN MANAJEMEN RISIKO PADA PROYEK KONSTRUKSI GEDUNG (Studi Kasus Proyek Apartemen Apple 3 Condovilla – Jakarta Selatan) - Muhammad Alfanny Setiawan; I Ketut Sucita; Bayu Sarwono (Construction and Material Journal, 2021)
The high complexity, the large workload, and the quite limited implementation time make apartment projects bound for uncertainty that poses various risks. Risk is a combination of the probability of an event and the consequences of the event, where the consequences that arise can be positive and negative and can affect the achievement of project targets. Therefore, it is necessary to conduct research in the form of identifying, assessing, analysing the risks that may occur in the project, and planning the responses of these risks. This research aims to find out how big the risks that occur in the project and the response to the dominant risks in the project. This research was descriptive and used qualitative risk analysis methods. Respondents in this research were directors, managers and engineers from the contractors, consultants and owners who are responsible for project implementation. Data were collected by distributing questionnaires and interviews.  The data analysis method used the severity index (SI) and the probability and impact matrix. The results of the analysis show that based on the 40 identified risks, when viewed from the cost aspect, there are 2 low risks, 17 moderate risks and 21 high risks. When viewed from the time aspect, there are 16 moderate risks and 24 high risks. When viewed from the quality aspect, there are 6 low risks, 25 moderate risks and 9 high risks. The risk responses are given to the dominant risks, namely those with a high category to the three aspects (Cost, Quality and Time), two aspects, or one aspect. Based on the 30 dominant risk variables, 16 risk variables were responded by reducing them, while the other 14 risk variables were responded by avoiding them. Keywords: Apartment Project, Risk Analysis, Risk Response.